Case report: Spontaneous lens absorption after the implantation of an implantable collamer lens - Liu, Xiaojing; Zeng, Qiulin; Lu, Ting; Wang, Min; Sun, Yong; Zhang, Jingfa (Frontiers in Medicine, 2023)
Background Spontaneous lens absorption is rare and usually occurs in eyes with certain syndromes, hyper-mature cataracts, and ocular trauma. The application of an implantable collamer lens (ICL) is widely performed in patients with high myopia for refractive correction. This study reports a case of spontaneous lens absorption after ICL implantation. Case summary A 23-year-old man was referred with complaints of poor vision in his left eye. The patient had undergone binocular ICL implantation for refractive correction of high myopia 1.5 years prior. Approximately 10 months later, he experienced a sudden loss of vision and pain in his left eye, which resolved spontaneously the next day without any treatment. Since then, the visual acuity in his left eye gradually decreased. At presentation, slit-lamp examination revealed an ICL in the posterior chamber of both eyes, with anterior capsular fibrotic proliferation and posterior capsular opacity, and the residual lens cortex sandwiched between the anterior fibrotic membrane and opacified posterior lens capsule in his left eye. The number of corneal endothelial cells in his left eye was 1,337, which was lower than before ICL implantation (2,902). The patient then underwent ICL extraction, anterior capsular capsulotomy, residual cortex aspiration, posterior capsular polishing, and intraocular lens implantation. Conclusions Spontaneous lens absorption may occur in patients with ICL implantation. Patients should undergo routine follow-ups after ICL implantation.